For the Law Shall Go Forth from Sefrou The literary Republic of David Ovadiah - Ohana, Michal Aziza (2024)
David Ovadiah was a Moroccan rabbi who played an active role in printing Jewish Moroccan manuscripts in the twentieth century. Scholars have identified "library and print awareness" as already developing among Moroccan rabbis toward the end of the nineteenth century. I argue that Ovadiah's efforts to print manuscripts exemplify the rise of such an awareness, a trend which grew particularly prominent in the first half of the twentieth century. The paratexts in Ovadiah's editions reveal the vital roles he played in the process of publication. Ovadiah the "publisher" was a cultural intermediary who participated in those "communication circuits" that connect writers to their readers. I further argue that Ovadiah's publication of rabbinic manuscripts from Sefrou and Fez and their consumption by a reading public express a traditional local identity as well as supracommunal and supraregional identities that began to develop in the late nineteenth century, reaching their peak in the colonial period and afterward.